1976
DOI: 10.1007/bf01086151
|View full text |Cite
|
Sign up to set email alerts
|

Comparative bioavailability: Eight commercial prednisone tablets

Abstract: Two four-treatment crossover bioavailability studies were performed in panels of 12 adult male volunteers with eight different commercial prednisone tablets. Plasma samples from the first study were assayed by radioimmunoassay for both prednisone and prednisolone. Plasma samples from the second study were assayed for prednisolone only. Statistical analyses of the data showed significant differences in the rate of appearance of prednisolone in plasma, but not in the amount converted to prednisolone. Some observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1976
1976
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…Gas-liquid chromatographic techniques have been used for prednisone (Pickup, 1973) and prednisolone (Bacon, 1969) estimations but lack the sensitivity required for determination in plasma following therapeutic doses, This criticism is true also of early attempts using spectrophotometry (Jenkins and Sampson, 1967;D'Arcy et al" 197 D, More sensitive competitive protein binding techniques (CPB) first developed by Murphy (1967) have been used for prednisolone estimations but lack specificity due to interference by endogenous corticosteroids, More recently published work has included a preliminary thin layer or paper chromatographic step to separate prednisolone from these endogenous steroids (English et al, 1974;Turner et al" 1973;Sandberg et al" 1970;Wilson et aI., 1975) or has made use of premedication with dexamethasone to suppress endogenous steroid production (Leclercq and Copinschi, 1974), The latter approach may, however, affect prednisolone pharmacokinetics by changing the transcortin binding capacity for the drug as a result ofthe lack of competition from endogenous cortisol (Angeli et aI., 1978), Radioimmunoassays (RIA) are commonly used for both prednisone (Colburn, 1974;Sullivan et aI., 1976;Schalm et al" 1976;Meikle et al" 1975) and prednisolone (Colburn and Buller, 1973;Sullivan et aI., 1974;Meikle et al" 1975;Schalm et al" 1976;Chakraborty et aI., 1976;Yotsumoto et al" 1974;Tembo et al" I 976a), Specificity problems have again been encountered due primarily to cross reactivity of prepared antisera with endogenous cortisone (prednisone assay) or cortisol (prednisolone assay), Cross reactivity has been reduced by dilution techniques (Colburn and Buller, 1975), by dexamethasone premedication (Sullivan et al" 1974(Sullivan et al" , 1975(Sullivan et al" , 1976, or by chromatography (Meikle et al" 1975), In terms of precision, the RIA (method of Sullivan et al" 1974) has been compared with a CPB method by Tembo et al, (1977a) and was shown to be inferior, Plasma from dexamethasone suppressed subjects was analysed, …”
Section: I Determination In Plasmaanalytical Techniquesmentioning
confidence: 95%
See 1 more Smart Citation
“…Gas-liquid chromatographic techniques have been used for prednisone (Pickup, 1973) and prednisolone (Bacon, 1969) estimations but lack the sensitivity required for determination in plasma following therapeutic doses, This criticism is true also of early attempts using spectrophotometry (Jenkins and Sampson, 1967;D'Arcy et al" 197 D, More sensitive competitive protein binding techniques (CPB) first developed by Murphy (1967) have been used for prednisolone estimations but lack specificity due to interference by endogenous corticosteroids, More recently published work has included a preliminary thin layer or paper chromatographic step to separate prednisolone from these endogenous steroids (English et al, 1974;Turner et al" 1973;Sandberg et al" 1970;Wilson et aI., 1975) or has made use of premedication with dexamethasone to suppress endogenous steroid production (Leclercq and Copinschi, 1974), The latter approach may, however, affect prednisolone pharmacokinetics by changing the transcortin binding capacity for the drug as a result ofthe lack of competition from endogenous cortisol (Angeli et aI., 1978), Radioimmunoassays (RIA) are commonly used for both prednisone (Colburn, 1974;Sullivan et aI., 1976;Schalm et al" 1976;Meikle et al" 1975) and prednisolone (Colburn and Buller, 1973;Sullivan et aI., 1974;Meikle et al" 1975;Schalm et al" 1976;Chakraborty et aI., 1976;Yotsumoto et al" 1974;Tembo et al" I 976a), Specificity problems have again been encountered due primarily to cross reactivity of prepared antisera with endogenous cortisone (prednisone assay) or cortisol (prednisolone assay), Cross reactivity has been reduced by dilution techniques (Colburn and Buller, 1975), by dexamethasone premedication (Sullivan et al" 1974(Sullivan et al" , 1975(Sullivan et al" , 1976, or by chromatography (Meikle et al" 1975), In terms of precision, the RIA (method of Sullivan et al" 1974) has been compared with a CPB method by Tembo et al, (1977a) and was shown to be inferior, Plasma from dexamethasone suppressed subjects was analysed, …”
Section: I Determination In Plasmaanalytical Techniquesmentioning
confidence: 95%
“…Studies with prednisone have been restricted to relative bioavailability assessments, comparing areas under plasma prednisone (Sullivan et al, 1976) or prednisolone concentration-time curves (Sullivan et aI., 1975(Sullivan et aI., , 1976Di Santo and De Sante, 1975) following administration of various commercial prednisone preparations. The results indicated equivalent bioavailability but significant differences in drug absorption rate were observed, determined by the tablet dissolution rate.…”
Section: Absorption and Bioavailabilitymentioning
confidence: 99%
“…[40], [41] Maximum serum concentrations occur within 1-2 h after administration of a single dose. [10], [11], [14], [31], [32], [35], [42][43][44] Food intake prolongs the time to peak concentration, but does not affect the extent of absorption. [45][46][47] No indication of existence of an absorption window was found in the literature.…”
Section: Absorption and Bioavailability (Ba)mentioning
confidence: 99%
“…One way to achieve this suppression is to administer dexamethasone. This procedure was used in studies on prednisone (10,11) and prednisolone (12,13). In these cases, dexamethasone administration was necessary since endogenous steroids cross react with the antiserums used in these radioimmunoassays.…”
mentioning
confidence: 99%